(x^2y^n)^2×(xy)^n-1=x^(n+3)y^(3n-1)
(x^2y^n)^2×(xy)^n-1
1个回答
相关问题
-
x^n+x^n-1y+x^n-2y^2+.+x^2y^n-2 +xy^n-1 +y^n=?
-
x^n+x^n-1y+x^n-2y^2+.+x^2y^n-2 +xy^n-1 +y^n=多少?
-
(xy^-1)^n/(-x^2y^-n)^2
-
1、分解因式:xy^n-xy^n-1+x^2y^n+1=___________
-
集合M={(x,y)|y=k(x-1)+1,xy∈R},N={(x,y)|x^2+y^2-2y=0,xy∈R},则M∩N
-
(m+n)x^n y^(m-2)(3xy^2+5x^2y)=21x^m y^(n+1)+35x^(m+1)y^n M和N
-
若X^n=2,y^n=3,则(xy)^n=( ),(x^2y^3)^n=( )
-
(x-y/x)2n×(x/y-x)2n+1 (n为正整数) 注:2n和2n+1是次幂
-
一道n阶导数问题1.已知y=e^(-x^2),而且y(n+2)+2xy(n+1)+2(n+1)y(n)=0 和y(n)=
-
n(x+y)=xy 怎么化成:(x-n)(y-n)=n^2